Sydenham’s Chorea with Silent Cardiac Lesions, Mimicking Encephalitis in a 13 Year Old Girl - Shakya, K. N.; Bhatta, A.; Yadav, A.; Gautam, U.; Basnet, S. (Kathmandu University Medical Journal, 2021)
Sydenham’s chorea is an uncommon neurological manifestation of rheumatic fever and has many and varied differential diagnosis. It may mimic encephalitis when presents as an isolated feature even when silent cardiac lesions are present. Early diagnosis, treatment and penicillin prophylaxis prevents recurrence and progression of cardiac lesions. Prompt symptomatic relief and alleviation of distress is obtained with therapeutic intervention. A case of rheumatic chorea with silent cardiac valve lesions which mimicked herpes simplex encephalitis with choreoathetosis, in a 13 year old girl is presented along with review of literature.